Unusual giant multilocular mesothelial cyst of mediastinum - Takehiko Manabe; Soichi Oka; Kenji Ono (Surgical Case Reports)
Abstract Background Intrathoracic mesothelial cysts are congenital lesions induced by the abnormal development of the pericardial coelom. There have been a few reports of giant mesothelial cyst of the superior mediastinum, but the preferred treatment remains a controversial topic. We herein report a rare case of successful removal of giant mesothelial cyst that was incidentally detected during a medical checkup. Case presentation A 53-year-old man with a feeling of mild chest tightness was referred to our hospital for the evaluation of an abnormal shadow of the mediastinum on chest X-ray. Computed tomography showed a multilocular, homogenous, large cyst in the superior mediastinum measuring 18 cm in size without contrast enhancement and with spotty calcification, and magnetic resonance imaging showed a low intensity on T1-weighted images and high intensity on T2-weighted images. Therefore, a cystic thymoma, thymic cyst, lymphangioma, cystic teratoma or pericardial cyst was suspected as the preoperative diagnosis. Despite mild symptoms, the patient underwent total thymectomy under median sternotomy for an appropriate diagnosis and treatment. The pathological diagnosis was giant multilocular mesothelial cyst. Conclusions Intrathoracic mesothelial cyst is a benign cyst and generally asymptomatic, but can sometimes induce critical chest clinical symptoms if untreated, depending on its size. In our case, complete surgical resection and a detailed pathological evaluation was effective for making the appropriate diagnosis and delivering treatment. In addition, an immunohistological evaluation is effective for diagnosing mesothelial cysts when it is difficult to distinguish the cyst from other cystic lesions.